Etude de l’effet de micro-onde sur la qualité organoleptiques et microbiologies de lait pasteurisé - DAMIM, SOUHYLA (My University, 2019)
Our study evaluated the organoleptic and microbiological quality of microwave-heated milk at different intervals as a function of time (1 min, 2 min, and 3 min) and for this reason we chose cow's milk, which is considered the most exploited to dairy production intended for human consumption. The results obtained in this study indicate that the sensory profiles of the majority of the milks are different and we note the increase of the intensity of certain descriptors you that the metallic taste and the decrease of other descriptors in particular the yellow color. After heating by microwaves for 1 min and 2 min, there is a rise in the microbial loads of the total coliforms sought 94,16,10 2 -68,102 CFU / ml and those faecal coliforms 17.5.10 2 - 22.8.10 2 CFU / ml respectively but which do not do not exceed the standards required by the official Algerian newspaper, and records a total absence of pathogenic germs (Staphylococcus) which gives us a good quality microbiological milk.
Keywords: pasteurized milk; microwave; organoleptic quality; microbiology quality